A horse with ossifying fibroma on mandible - Mustafa Arıcan; Mustafa Ortatatlı; Hanifi Erol; Özgür Kanat; Orhan Yavuz (Eurasian Journal of Veterinary Sciences)
In this case report, 7 years old, female, weighted 300 kg, the Rahvan horse which brought to Department of Surgery, Faculty ofVeterinary Medicine Clinic with, ossifying fibroma at the right ramus mandible; clinical, radiological, laboratory and histopathological findings were presented.